ASPEK BUDAYA DALAM NOVEL ULID KARYA MAHFUD IKHWAN: TINJAUAN POSTMODERNISME JEAN FRANCOIS LYOTARD - Hernani, Hernani; Mahmudah, Mahmudah; Asri, Aswati (Neologia: Jurnal Bahasa dan Sastra Indonesia, 2020)
This study aims to describe the cultural aspects of Mahfud Ikhwan's novel Ulid. This type of research is descriptive qualitative research. The results of research in the novel Ulid by Mahfud Ikhwan show that there are various situations that describe postmodernist behavior which is more dominated by the nature of irony found in situations such as natural disasters, the economy and things that are contrary to feelings. The next aspect is Camp's behavior which is described in the form of deception of appearance, attitude, objects and characteristics. Pastiche is expressed through situations related to the character's behavior and expectations in the past. Eclecticism is depicted in the form of a combination of objects, language and food. The parody aspect is expressed in the form of an expression of feelings of satisfaction, displeasure and discomfort.